Use of natural products to improve meat quality of sheep reared in the Mediterranean environment - Luciano G. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Recently, research in small ruminant feeding has been focusing on the use of natural plant-derived molecules, such as phenolic compounds (PCs) and essential oils (EOs). While it is necessary that such strategies do not compromise animal productivity, evidence has been provided for potential positive effects of feeding animals with these plant bioactive compounds on meat quality traits, such as intramuscular fatty acid composition, sensory properties and oxidative stability. The potential mechanisms of action of these bioactive molecules have been suggested by a number of studies in which selected plant extracts or purified compounds were studied in vitro or were fed to animals. The results of these studies highlighted, for instance, a possible ability of dietary PCs and EOs to reduce the extent of the ruminal biohydrogenation of polyunsaturated fatty acids, with a consequent increase in the content of desirable unsaturated fatty acids in meat. Dietary PCs can exert other effects upon the ruminal metabolism leading, for instance, to the reduction of the production of odour-active compounds, such as skatole and indole, responsible for conferring on the meat unpleasant flavours when present at high concentration. Also, the strong antioxidant properties of both PCs and EOs make them good candidates to replace synthetic antioxidants in ruminant diets, with positive effects being observed on the reduction of the oxidative deterioration of meat nutritional and sensory quality. However, it is important to stress that these potential activities need to be regarded in the light of the great variability in the chemical nature of these compounds and of the concentration at which they actually exert effects when ingested by small ruminants. These considerations are of importance because the practical interest in the dietary administration of such compounds to ruminants lies on the fact that they are naturally occurring in plant biomasses typically produced in the Mediterranean areas, such as agro-industrial wastes and by-products. Nowadays, the replacement of conventional feedstuffs with these low-cost and locally available feeds might represent an effective strategy to promote low input production systems and to cope with the increasing costs of conventional systems. Some of these feed resources are known for containing PCs and EOs (e.g. olive, citrus and aromatic plant by-products, carob pulp and others) and research has demonstrated that their inclusion into small ruminant diets positively affects meat quality. However, the direct attribution of such effects to the presence of PCs and EOs should be made with caution, because the chemical nature of these compounds, their concentration and the presence of other molecules (such as unsaturated fatty acids and antioxidant vitamins) need to be taken into account.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)